Age at Menarche and Its Relation to Ages at Marriage, First-Birth and Menopause among Rural Nepalese Females - Aryal, Tika R (Nepal Journal of Science and Technology, 2012)
The aim of this paper is to study age at menarche and its relation to ages at marriage, first birth and menopause among resident of rural Nepalese females. Data are taken from a sample survey of Palpa and Rupandehi districts. Median ages at marriage, first birth and menopause were found to be 17, 19 and 46 years respectively. It was found that ages related events (menarche, marriage, first birth and menopause) were found to be largely inter-related. The waiting time at menarche for getting married was found to be about two years, and the correlation between age at menarche and age at marriage is statistically significant. Transition probability matrix also revealed that ages at menarche, marriage, first birth and menopause were found to be statistically associated. Finally, the onset of menarche among females signals that they will be ready for marriage and thereby giving birth of child. These findings may help planners and policy-makers for designing proper policy in improving reproductive health and reproductive rights of females along with controlling the level of fertility in a country. DOI: http://dx.doi.org/10.3126/njst.v12i0.6513 Nepal Journal of Science and Technology 12 (2011) 276-285